2021
DOI: 10.1038/s41598-021-82308-y
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid stabilizes Staphylococcus aureus biofilm by impairing the agr quorum-sensing system

Abstract: Salicylic acid (SAL) has recently been shown to induce biofilm formation in Staphylococcus aureus and to affect the expression of virulence factors. This study was aimed to investigate the effect of SAL on the regulatory agr system and its impact on S. aureus biofilm formation. The agr quorum-sensing system, which is a central regulator in S. aureus pathogenicity, plays a pivotal role in the dispersal of S. aureus mature biofilms and contributes to the creation of new colonization sites. Here, we demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 64 publications
(92 reference statements)
3
27
0
Order By: Relevance
“…A previous report demonstrated that deletion of multiple lytic genes, such as prophages in Gram-positive bacteria, e.g., Bacillus subtilis , can prevent cell lysis and enhance biomass 80 . A recent study showed that the salicylic acid interferes with the regulatory agar QS system in pathogenic Staphylococcus aureus , consequently negatively affecting autolysis 58 . The delay of autolysis in DT mutants of DSM 7029 was probably due to the deletion of lytic genes or their regulatory genes during the genome reduction procedure, e.g., lysozyme or XRE family transcriptional regulator-coding genes (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report demonstrated that deletion of multiple lytic genes, such as prophages in Gram-positive bacteria, e.g., Bacillus subtilis , can prevent cell lysis and enhance biomass 80 . A recent study showed that the salicylic acid interferes with the regulatory agar QS system in pathogenic Staphylococcus aureus , consequently negatively affecting autolysis 58 . The delay of autolysis in DT mutants of DSM 7029 was probably due to the deletion of lytic genes or their regulatory genes during the genome reduction procedure, e.g., lysozyme or XRE family transcriptional regulator-coding genes (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To verify the effect of boron derivative on biofilm formation, the growth curve of recombinant E. coli was detected ( Figure 2 a). This addition had no effect on the strain’s growth, which had reached a stable phase after 15 h. Therefore, the period of the highest biofilm index of recombinant E. coli was at the initial stage of stable growth of the strain, which corresponded to the period with the highest AI-2 activity in previous studies [ 25 ]. Figure 2 b illustrates the growth of recombinant E. coli biofilm with H 3 BO 3 , NaBO 2 , and NaBO 3 .…”
Section: Resultsmentioning
confidence: 76%
“…Colony spreading of E. coli was performed as described in 20,21 . Isolates were grown in Luria-Bertani broth for 24 hours.…”
Section: Colony Spreading Of E Colimentioning
confidence: 99%